Malgaigne Fracture in Childhood: A Case Report and Review of Literature. Issue 4 (January 2016) - Kaya, Mustafa; Yaldiz, Can; Ceylan, Davut
Abstract : Abstract: Sacrum fractures are rare pathologies seen after spinal traumas. The incidence of a sacral fracture after trauma is 0.6% in childhood. A Malgaigne fracture is composed of fractures and dislocations of the anterior and posterior regions of the pelvis. This is the first reported case of Malgaigne fracture during childhood. A 12-year-old girl was admitted to our emergency room after having suffered a fall. Radiological tests revealed a zone 3 sacral fracture according to the Denis scoring, a subtype 2 sacral fracture according to the Roy-Camille classification, and a detachment in the symphysis pubis. Appropriate load distribution through a bilateral L5–S1–S2 transpedicular screw and a bilateral iliac wing screw, as well as neural decompression were performed together with an S1–S2 total laminectomy. It is very difficult to make a generalization for treatment of sacral fractures and Malgaigne fractures in childhood due to the small number of patients. Each patient should be individualized and lumbosacroiliac instability should be treated.